Intersexo e (in)visibilidade: cidadania e saúde na busca do registro geral de identificação (RG) - Lima, Shirley Acioly Monteiro de [UNIFESP] (2014)
The objective of this thesis is to ethnograph the itinerary of intersex people in search of a new Identification Card (ID). In order to regularize the birth certificate and I.D, intersex people need to seek medical endorsement, go through surgical interventions to change their body and/or obtain medical reports. This ethnography follows two of these trajectories and focused on the encounter and the relation established by adult intersex people and the groups involved on their care: social, medical and law. This thesis is about their path, the process of affirmation of an identity by which they wanted to be known and socially called. This process demonstrates that the restriction of knowledge about intersexuality within the biomedical sphere, has kept intersex people invisible to the State or, at most, tied to pathologized diagnoses, which constrain their way out of the health system.